Paleogene microfossils from the submarine debris flows in the Skole basin (Polish and Ukraine Outer Carpathians) - Szydło, Andrzej; Garecka, Małgorzata; Jankowski, Leszek; Malata, Tomasz (Geology, Geophysics and Environment, 2014)
Biostratigraphic analysis of fossils material has allowed the documentation of sediment gravity flows in the Skole basin during the Paleocene and Eocene times, and also in the Eocene-Oligocene transition. This most external basin of the NE Outer Carpathians was a marginal sea especially sensitive to geotectonic instability and relative sea-level change, favoring the development of down slope movements at these times. The dominance of calcareous forms in foraminifera, and a large share of redeposited species among the nanno- and microfossils indicate a close relationship of sediments containing them with the shelf environment and documents not too long transport. Additionally the recycled forms are often well preserved, indicating that the rock contained in flows were only plasticized and hydrated while the material itself was not a subject of significant mechanical processing in contrast to that one, which directly documented down slope moving. The latter forms are bad preserved and their fossil remains are usually corroded, partially dissolved and broken during this process. In addition, the planktonic forms including foraminifera, calcareous dinocysts and nannoplankton allow documenting the time of the final deposition of the sediment transported on slope.